2020
DOI: 10.1007/s11468-020-01298-1
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Engineering Via Complex Patterns of Circular Nano-Object Miniarrays: II. Concave Patterns Tunable by Integrated Lithography Realized by Circularly Polarized Light

Abstract: The use of circularly polarized beams in interferometric illumination of colloid sphere monolayers enables the direct fabrication of rectangular patterns composed of circular nanohole miniarrays in metal films. This paper presents a study on the spectral and near-field effects of complex rectangular patterns consisted of a central nanoring and slightly rotated satellite nanocrescents in azimuthal orientations, which promote coupling between localized and propagating plasmons. To inspect the localized modes sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
0
8
0
1
Order By: Relevance
“…A kolloidgömb monorétegek interferáló nyalábokkal történő kivilágításával megvalósítható integrált litográfiával létrehozható komplementer konkáv és konvex nano-objektumokból felépülő struktúrák spektrális és közeltérbeli hatásait vizsgáltuk. Olyan komplex struktúrákat tanulmányoztunk, amelyek a 100 nm átmérőjű arany kolloidgömbök 60° azimutális orientációban elhelyezett monorétegének 400 nm-es cirkulárisan polarizált fénnyel történő kivilágításával hozhatók létre, két 12.83° szögben beeső interferáló nyalábbal (5. ábra) [5,6].…”
Section: Komplex Plazmonikus Struktúrák Emitterek Erősítéséreunclassified
“…A kolloidgömb monorétegek interferáló nyalábokkal történő kivilágításával megvalósítható integrált litográfiával létrehozható komplementer konkáv és konvex nano-objektumokból felépülő struktúrák spektrális és közeltérbeli hatásait vizsgáltuk. Olyan komplex struktúrákat tanulmányoztunk, amelyek a 100 nm átmérőjű arany kolloidgömbök 60° azimutális orientációban elhelyezett monorétegének 400 nm-es cirkulárisan polarizált fénnyel történő kivilágításával hozhatók létre, két 12.83° szögben beeső interferáló nyalábbal (5. ábra) [5,6].…”
Section: Komplex Plazmonikus Struktúrák Emitterek Erősítéséreunclassified
“…3b, c and Fig. 4-8/b) [49][50][51]. Localised plasmon resonances on the nanorings and nanocrecents are distinguished by using r and c in the abbreviations.…”
Section: Numerical Modeling and Characterization Of Patterns Consisti...mentioning
confidence: 99%
“…In our present study the size parameters of the inspected ring-and crescentshaped nano-objects, the ε opening angle and the ω orientation of the nanocrescents, as well as the pattern periods are equal to those of the complementary concave patterns described in our corresponding papers, in order to ensure comparability [50,51]. Namely, uniform nanorings with 10 nm and 46 nm (50 nm) inner and outer diameters were inserted into the hexagonal pattern (artificial rectangular pattern of singlet nanorings and both rectangular patterns of analogue miniarrays).…”
Section: Patterns Achievable In Different Illumination Configurationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies, illumination by linearly polarized light was realized to compare the transmittance and reflectance of complementary convex and concave complex pattern configurations that can be fabricated by integrated colloid-sphere and interference lithography [44][45][46] . We demonstrated that in the case of linearly polarized light illumination, the convex transmittance subtracted from unity (reflectance) and the concave inverted rectified reflectance (rectified transmittance) extracted from the polarization unspecific power-outflow read-out, are complementary [44][45][46] . In our present study, the polarization specifically read-out transmittance signals of Babinet complementary single and multilayers illuminated by linearly and circularly polarized light are determined via Jones matrix elements to demonstrate metamaterial capabilities [47][48][49] .…”
mentioning
confidence: 99%